Pemahaman Etika Komunikasi Manusia dengan Mesin: Studi Kasus Pemahaman Etika Penggunaan ChatGPT dalam Pengerjaan Tugas di Kalangan Mahasiswa Ilmu Komunikasi UNS - Anang Tri Budianto; Prahastiwi Utari (Universitas Sebelas Maret (UNS), 2025)
The advancement of artificial intelligence (AI) technology has significantly transformed the academic world, particularly in how students complete their assignments. One of the most widely used technologies is ChatGPT, an AI-based chatbot capable of generating text automatically. The use of ChatGPT in academic settings creates a dilemma between efficiency benefits and potential misuse, such as plagiarism and the decline of students’ critical thinking skills. Therefore, this study aims to analyze how Communication Science students at Universitas Sebelas Maret (UNS) understand human-machine interaction in an academic context and the ethical implications that arise. The urgency of this research lies in the need for a deeper understanding of AI's impact on academic integrity, particularly in aspects of honesty and responsibility in assignment completion. This study employs a qualitative research method with a case study approach. The theoretical framework used is Human-Machine Communication (HMC), which examines human interaction with AI through three main dimensions: metaphysical, symbiotic, and relational. Data were collected through in-depth interviews with 10 students from different semesters who actively use ChatGPT for academic tasks. The results indicate that students utilize ChatGPT for reference searches, assignment writing, and paraphrasing. However, there is a tendency not to verify the accuracy of the information provided by ChatGPT, posing a risk to academic validity. Furthermore, the study found ambiguity in students' understanding of academic ethics, where some still perceive using ChatGPT without attribution as acceptable. Further analysis reveals that students’ interactions with ChatGPT reflect a symbiotic relationship, in which AI is not merely a tool but also influences their academic thinking patterns and habits. This study concludes that while ChatGPT provides convenience in academic work, its use requires clear regulations and improved digital literacy. Students must develop a stronger understanding of academic ethics to responsibly integrate AI technology without compromising scientific integrity and originality. Additionally, educational institutions should consider policies regulating AI usage to prevent academic misconduct.